Adaptation of the Texas Christian University Organisational Readiness for Change Short Form (TCU-ORC-SF) for use in primary health facilities in South Africa ... - Brooke-Sumner, Carrie; Petersen-Williams, Petal; Wagener, Emma; Sorsdahl, Katherine; Aarons, Gregory; Meyers, Bronwyn (Dryad, 2021)
Objectives: The Texas Christian University Organisational Readiness for Change Scale (TCU-ORC) assesses factors influencing adoption of evidence-based practices. It has not been validated in low- and middle-income countries (LMIC). This study assessed its psychometric properties in a South African setting with the aim of adapting it into a shorter measure. Methods: This study was conducted in 24 South African primary health care clinics in the Western Cape Province. The TCU-ORC and two other measures, the Organisational Readiness to Change Assessment (ORCA) and the Checklist for Assessing Readiness for Implementation (CARI) were administered. The questionnaire was re-administered after 2 weeks to obtain data on test-retest reliability. Three hundred and ninety-five surveys were completed: 281 participants completed the first survey, and 118 re-completed the assessments. Results: We used exploratory factor analysis (EFA) to identify latent dimensions represented in the data. Cronbach’s alpha for each subscale ... : Data collection took place from July to December 2018 at the 24 facilities that participated in the MIND trial. Following a workshop that introduced the study in the facilities, health service employees (managers and staff) were requested to complete a paper-based, English language self-report survey, after granting written informed consent. English is the official language of business of the South African health system. Participants at workshops included facility managers, operational managers, medical officers, psychiatric nurses, general nursing staff from the chronic disease care team, and lay counsellors. Between one and two weeks after the workshop, Project MIND fieldworkers asked a sub-sample of participants (convenience sample) from each facility to re-complete the paper-based survey comprising the ORC measures to enable assessment of test-retest reliability. These fieldworkers also approached nursing staff directly to fill in the questionnaire to gain enough responses for the first survey. In total, ...